2007
DOI: 10.1093/nar/gkm1120
|View full text |Cite
|
Sign up to set email alerts
|

Role of poly (A) tail as an identity element for mRNA nuclear export

Abstract: Different RNA species are rigorously discriminated and exported by distinct export factors, but this discrimination mechanism remains largely unknown. We previously showed, by RNA microinjection experiments, that intronless mRNAs are discriminated from U snRNAs based on their difference in RNA length. However, it was unclear how they are discriminated in the natural situation in which their nascent transcripts emerge progressively during transcription. We hypothesized that transcription from the corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 66 publications
2
69
0
1
Order By: Relevance
“…We constructed BORG expression cassettes that contained a nonendogenous cytomegalovirus (CMV)-based promoter, followed by the sequence of mature BORG transcript completely lacking the intronic sequences. To enable the resulting intronless transcript to interact with the nuclear export machinery, we in- cluded the genomic sequences ϳ180 nucleotides downstream of the cleavage site of BORG RNA, which contained the GU-rich sequence required for efficient polyadenylation, as it has been shown that polyadenylation enables the efficient export of intronless transcripts (32)(33)(34)(35). In addition, the presence of the native polyadenylation signal, cleavage site, and downstream elements ensured that the 3=-end processing of the transgene-derived BORG transcripts would be similar to that of the endogenous BORG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We constructed BORG expression cassettes that contained a nonendogenous cytomegalovirus (CMV)-based promoter, followed by the sequence of mature BORG transcript completely lacking the intronic sequences. To enable the resulting intronless transcript to interact with the nuclear export machinery, we in- cluded the genomic sequences ϳ180 nucleotides downstream of the cleavage site of BORG RNA, which contained the GU-rich sequence required for efficient polyadenylation, as it has been shown that polyadenylation enables the efficient export of intronless transcripts (32)(33)(34)(35). In addition, the presence of the native polyadenylation signal, cleavage site, and downstream elements ensured that the 3=-end processing of the transgene-derived BORG transcripts would be similar to that of the endogenous BORG.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on subcellular localization of RNAs have mostly focused on the nuclear export of protein-coding RNAs, in which 5= capping, splicing, and deposition of the exon junction complex and polyadenylation play the major roles, although the involvement of some RNA sequence motifs has also been documented (27)(28)(29)(30)(31). In intronless RNAs, polyadenylation seems to play the dominant role in export of RNAs to the cytoplasm (32)(33)(34)(35). In contrast, the mechanism of nuclear retention and import of RNAs is poorly understood, except in the case of a few highly abundant classes of housekeeping RNAs.…”
mentioning
confidence: 99%
“…Given that addition of a poly(A) tail can be sufficient to target mRNAs for nuclear export (Brodsky and Silver 2000;Fuke and Ohno 2008), we first investigated whether there were any changes in subcellular localization of these RNAs in knockdown cells. To this end, we separated cell compartments into cytoplasmic, nuclear-soluble, and chromatin fractions.…”
Section: Depletion Of Mtr4/zfc3h1 Causes Cytoplasmic Accumulation Of mentioning
confidence: 99%
“…13,14 We also found that the presence of the poly A tail in the transcript can function as another mRNA identity element. 12 If a poly A tail of an appropriate length was present on the transcript, the transcript was committed to the mRNA export pathway in a dominant manner, even when the transcript without the poly A tail was too short to behave like an mRNA, indicating that the poly A tail either contributes to increasing the RNA length or functions as a platform that specifically recruits mRNA export factors.…”
Section: Identity Elements Used In Mrna Exportmentioning
confidence: 99%
“…However, contrary to our hypothesis, whether transcription occurred from the mRNA-or U-snRNA-type promoter did not influence the discrimination process. 12 Instead, the features of the transcribed RNAs, rather than the ways they were transcribed, were important in determining the identities of the RNAs for nuclear export.…”
Section: Identity Elements Used In Mrna Exportmentioning
confidence: 99%